Penerapan Pendekatan Project Based Learning dalam Pembelajaran Matematika Sekolah Dasar pada Mahasiswa PGSD FKIP Universitas Jambi Semester Ganjil 2021/2022 - Violita Zahyuni; Yantoro Yantoro; Suci Hayati (Peneliti.net, 2021)
Taking into account its unique and comprehensive characteristics, the Project Based Learning model has the potential to meet the demands of students' mathematics learning in elementary mathematics learning. Project Based Learning model helps students in learning. This research is using Classroom Action Research (CAR). Classroom Action Research is a research that describes the occurrence as a cause and effect of the treatment, as well as describes what happens when the treatment is given. In this study, the project based learning model is expected to be a solution and innovation in the learning process that has characteristics and provides problems or asks the urgency of competencies to be studied for a prospective elementary school teacher to students, facilitating students to design a process to determine solutions to problems. or challenges posed, and facilitate students collaboratively in unliterating students to take responsibility for accessing and managing information to solve problems.